First Records of Morphological Diversity and Ecology of Periphytic Cyanobacteria from Tukun River, Penang Forest Reserve, Malaysia - Asmimie Asmawarnie Azizan; Ranina Radzi; Wan Maznah Wan Omar; Peter Convey; Faradina Merican Mohd Sidik Merican (Tropical Life Sciences Research, 2020)
Despite the abundance of streams and rivers in Malaysia, the algal communities of these lotic ecosystems have remained largely unstudied. In a one-year floristic survey conducted from December 2014, 24 cyanobacterial morphospecies were identified for the first time from Tukun River, Penang Forest Reserve. Ten morphospecies were identified directly from field specimens while the remaining 14 morphospecies were identified only in cultures derived from the field samples. A total of 17 morphospecies; Leptolyngbya cf. boryana, L. cf. foveolarum, L. valderiana, Chroococcus cf. cohaerens, C. cf. disperses, C. cf. membraninus, C. cf. minutus, C. cf. varius, Gloeocapsopsis cf. crepidinum, Geitlerinema cf. tenuius, Phormidium simplicissimum, Dolichospermum sp., Fischerella sp., Homoeoptyche repens, Nematoplaca inscrustans, Scytonema hofmanii and S. stuposum are new records for Malaysia. Crusts were the most dominant macroscopic forms (seven morphospecies) followed by mats (three morphospecies). Scytonema was the most frequently encountered genus, occurring at 8/9 sampling sites. The presence of heterocytous cyanobacteria (S. stuposum, S. hofmanni) in 8/9 sampling sites is consistent with the low nitrate levels (< 0.74 mg/L) recorded throughout the study stream. Chroococcales were dominant in both upper and middle parts of the stream. The morphospecies present showed distinct distribution patterns despite apparently minimal variations in ecological parameters such as temperature, dissolved oxygen, pH and conductivity between the sampling sites. This study provides important new baseline information in understanding the diversity of periphytic cyanobacteria not only in Penang Island but more widely in Malaysia. This information can make a useful contribution in biomonitoring stream health.